Computer Surveillance System (International Journal of Engineering and Computer Science, 2014)
In this paper we will characterize different ways to keep track of all the activity done on computer and how these tracked records are saved and further accessible to administrator. Computer Surveillance System gives parent’s opportunity to keep an eye on their kid to check what their kid is doing in their absence. Also Computer Surveillance System gives opportunity to manager to check their employees whether they are doing their work properly or busy in doing chatting etc